2013
DOI: 10.1128/ec.00093-13
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Reorganization of Saccharomyces cerevisiae Enolase To Alter Carbon Metabolism under Hypoxia

Abstract: c Hypoxia has critical effects on the physiology of organisms. In the yeast Saccharomyces cerevisiae, glycolytic enzymes, including enolase (Eno2p), formed cellular foci under hypoxia. Here, we investigated the regulation and biological functions of these foci. Focus formation by Eno2p was inhibited temperature independently by the addition of cycloheximide or rapamycin or by the single substitution of alanine for the Val22 residue. Using mitochondrial inhibitors and an antioxidant, mitochondrial reactive oxyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
78
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(85 citation statements)
references
References 82 publications
7
78
0
Order By: Relevance
“…Taken together, we confirmed G body localization of 31 out of 33 candidates identified by mass spectrometry, 29 of which were new G body components. Two factors (Fas1p and Fas2p) that we identified were also validated by colocalization by Miura et al, who also identified 8 unique factors by colocalization studies of their mass spectrometry candidates (Miura et al, 2013, S3D). …”
Section: Resultssupporting
confidence: 71%
See 3 more Smart Citations
“…Taken together, we confirmed G body localization of 31 out of 33 candidates identified by mass spectrometry, 29 of which were new G body components. Two factors (Fas1p and Fas2p) that we identified were also validated by colocalization by Miura et al, who also identified 8 unique factors by colocalization studies of their mass spectrometry candidates (Miura et al, 2013, S3D). …”
Section: Resultssupporting
confidence: 71%
“…In this study, we characterize hypoxia-induced, non-membrane bound granules comprised of glycolytic enzymes that we refer to as glycolytic bodies,” or “G bodies,” in the budding yeast S. cerevisiae and in human hepatocarcinoma cells, confirming and expanding previous studies (Miura et al, 2013, Jang et al, 2016). Cells unable to form G bodies exhibit growth defects, specifically in hypoxia.…”
Section: Introductionsupporting
confidence: 85%
See 2 more Smart Citations
“…32 Under hypoxic conditions, enolase in yeast cells was demonstrated to form punctate structures with glucokinase, glucose-6-phosphate isomerase, phosphofructokinase, aldolase, triose phosphate isomerase, glyceraldehyde-3-phosphate dehydrogenase, phosphoglycerate mutase, and pyruvate kinase. 33 In addition, F-actin was found to provide docking sites for the organization of hexokinase, glucose-6-phosphate isomerase, triose phosphate isomerase, glyceralde-hyde-3-phosphate dehydrogenase, phosphoglycerate mutase, and aldolase in yeast. 34 Particularly, their association with F-actin appears to increase individual enzyme activities while protecting against the inhibitory effects of trehalose in yeast cells.…”
Section: Glucose Metabolismmentioning
confidence: 99%